2006
DOI: 10.1590/s1517-86922006000500008
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento multidisciplinar reduz o tecido adiposo visceral, leptina, grelina e a prevalência de esteatose hepática não alcoólica (NAFLD) em adolescentes obesos

Abstract: The aim of this study was to assess the changes promoted by a multidisciplinary therapy in ghrelin and leptin concentrations, visceral adiposity and non-alcoholic fat liver disease-NAFLD, in obese adolescents. A total of 28 obese adolescents, 16 girls (BMI 34.58 ± 3,86 wt /ht 2 ) and 12 boys (BMI 37.08 ± 3.17 wt /ht 2 ), aged between 15 and 19 years old, was evaluated to leptin, ghrelin and insulin concentrations, visceral adiposity and NAFLD through ultrasonography. The results showed a significant decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 37 publications
2
22
0
21
Order By: Relevance
“…Considerando-se que o patrimônio genético da espécie humana não sofreu mudanças significativas, certamente os fatores ambientais podem explicar esta pandemia. Acredita-se que mudanças no comportamento alimentar e a adoção de hábitos de vida sedentários podem atuar sobre genes de susceptibilidade sendo determinante ao crescimento da obesidade no mundo 4 . Entretanto, as causas exatas ainda são desconhecidas e continuam em debate 5 .…”
Section: Introductionunclassified
“…Considerando-se que o patrimônio genético da espécie humana não sofreu mudanças significativas, certamente os fatores ambientais podem explicar esta pandemia. Acredita-se que mudanças no comportamento alimentar e a adoção de hábitos de vida sedentários podem atuar sobre genes de susceptibilidade sendo determinante ao crescimento da obesidade no mundo 4 . Entretanto, as causas exatas ainda são desconhecidas e continuam em debate 5 .…”
Section: Introductionunclassified
“…[17][18][19][20] Table I contains details of each study, including the country where the intervention was conducted, the focus and duration of the intervention, frequency of sessions, effect sizes for primary outcomes, and study designs. The total number of sessions for the entire duration of the intervention ranged, from 4 to 120 with a median of 41 sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Every study had significant changes in BMI, three had significant changes in weight, 17,18,20 and one had a significant change in percent body fat.…”
mentioning
confidence: 98%
“…Within this context, it is important to mention that a recent study of our study group (53) , demonstrated that the majority of the obese female adolescents who registered in our Multidisciplinary Program for obesity treatment, presented exacerbated hyperleptinemia. Such fact could suggest resistance to this hormone's action derived from alterations in their receptors, which would result in lower thermogenesis and MRM reduction of these patients.…”
Section: Bmr In Obese Subjects and Leptinmentioning
confidence: 90%